Hepatitis B-related knowledge and vaccination in association with discrimination against Hepatitis B in rural China. Issue 1 (2nd January 2016) - Yu, Lijie; Wang, Jian; Zhu, Dawei; Leng, Anli; Wangen, Knut R
Abstract : Hepatitis B virus (HBV) remains a challenging public-health issue in China. Hepatitis B carriers and patients suffer not only physically but also experience strong discrimination and stigma. China's rural population is 629 million. Thus, there is a great need to understand the situation surrounding HBV-related discrimination in everyday life in rural China. We studied 6, 538 participants (≥18 y old) from 42 villages across 7 provinces (districts). Many studies have addressed discrimination against those with human immunodeficiency virus (HIV) and hepatitis C virus (HCV). However, few studies have addressed HBV-related discrimination. We found that the fear of HBV infection, not lack of knowledge about it, predominantly leads to HBV-related discrimination (although limited knowledge is also a cause). Notably, receiving the HBV vaccination contributes to reduced discrimination. In addition, the existence of fewer misunderstandings about false HBV transmission routes plays a more important role in discrimination than does understanding of true HBV transmission routes. Therefore, to reduce HBV-related discrimination, policy makers should consider eliminating HBV-related fear, strengthening adult HBV immunization programs, developing large-scale education dissemination about HBV transmission routes and non-transmission routes, and paying greater attention to target populations.